ANALYSES OF ANTHROPOMETRICS, ADIPOSITY AND PHYSICAL FITNESS INDEXES BETWEEN SEXES IN THE AGE OF 11 YEARS OLD (Fiep Bulletin - online, 2014)
OBJECTIVE: to examine the differences between the anthropometrics, adiposity and physical fitness indexes between boys and girls in the same chronological age. METHODS: the sample was composed by 28 boys and 42 girls in the age of 11 years and enrolled in a public school of Araucaria-PR. Fat percentage was calculated by the equation of BOILEAU et al. (1985), sit-and-reach test and hand grip test were performed according to JOHNSON and NELSON (1986) and SAFRIT (1986) and VO2 max was estimated using 20-m Shuttle Run test developed by LÉGER et al. (1986). Resting blood pressure (BP) was collected by the procedures suggested by ACSM (2003). Descriptive statistic and independent t test of Student were used to examine the differences of the variables studied between sexes, (p
Keywords: adiposity; physical fitness; sexes